Chronic Prostatitis / Chronic Pelvic Pain Syndrome - problematic common disease. Current knowledge on etiology, diagnosis and treatments - Wojciech Żołyniak; Ziemowit Żaba; Paweł Warzyszak; Róża Małek; Maria Milczek; Izabela Hawranik; Aleksandra Lisowska; Mikołaj Tomasik; Szymon Niski; Mateusz Skrzypek (Nicolaus Copernicus University in Toruń, 2022)
Introduction: Nonbacterial prostatitis (CNP) also known as chronic pelvic pain syndrome (CPPS) is a condition with an incompletely understood etiology. Chronic prostatitis is diagnosed when symptoms of prostatitis persist for more than 3 months and it is difficult to treat. The causes are not fully understood. Among the many possible causes are stress, psycho-emotional disorders, hormonal disorders and autoimmune disorders. The main symptom is pain usually felt in the perineum, at the base of the penis, in the anal area, sometimes over the pubic symphysis. This pain can radiate to the penis and scrotum.   Aim of the study: Summary of current knowledge on the treatment of Chronic Prostatitis/Chronic Pelvic Pain Syndrome.   Material and methods: Review of PubMed articles using the following keywords: "nonbacterial chronic prostatitis", "abacterial chronic prostatitis" and "chronic pelvic pain syndrome".   Results: Complete cure in non-bacterial chronic prostatitis is rare. Due to the lack of knowledge of the cause of chronic prostatitis, there is no effective treatment for this disease. Although the pathogen is rarely found in the patients studied, many patients show improvement after antibiotic therapy. In addition, anti-inflammatory drugs, alpha blockers and neuromodulators are used. Physical therapy also has proven benefits in relieving symptoms.   Conclusion: CNP is a frustrating disease for many doctors and patients. Although it is not yet completely understood, we have made significant progress in the evaluation and treatment of this disease over the past several decades. Physicians need to move away from outdated algorithms that often result in endless courses of antibiotics and embrace multimodal therapy, which provides better results than other treatment strategies.